2012
DOI: 10.2478/10004-1254-63-2012-2185
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV in Inflammatory Bowel Diseases (DPP IV/CD26)

Abstract: Dipeptidil-peptidaza IV (DPP IV/CD26) i upalne bolesti crijevaUpalne bolesti crijeva (Crohnova bolest, ulcerozni kolitis, nedeterminirani kolitis) skupina su kroničnih autoimunosnih upalnih bolesti obilježenih ponavljanim upalama različitih dijelova gastrointestinalnog trakta koje su važan javnozdravstveni problem današnjice. Unatoč brojnim temeljnim i kliničkim istraživanjima etiologija ovih bolesti, kao i sama patogeneza upale ostaju nedovoljno razjašnjene. Dosadašnja su istr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 148 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Regarding a catalytic function of DPP-4 on GLP-1 and GLP-2, previous studies have demonstrated that DPP-4 can act as an immune regulator via its expression on immune cells and the ability to cleave biologically active chemokines and cytokines. Hence, DPP-4 involvement in the pathogenesis of colitis has been proposed ( 96 ). The involvement of DPP-4 might depend on two major pathways: the catalytic function and non-catalytic function ( 38 , 73 , 97 ).…”
Section: Inhibition Of Dpp-4 Function In Ibdmentioning
confidence: 99%
“…Regarding a catalytic function of DPP-4 on GLP-1 and GLP-2, previous studies have demonstrated that DPP-4 can act as an immune regulator via its expression on immune cells and the ability to cleave biologically active chemokines and cytokines. Hence, DPP-4 involvement in the pathogenesis of colitis has been proposed ( 96 ). The involvement of DPP-4 might depend on two major pathways: the catalytic function and non-catalytic function ( 38 , 73 , 97 ).…”
Section: Inhibition Of Dpp-4 Function In Ibdmentioning
confidence: 99%
“…The inhibition of all of the above mentioned enzymes by peptides is associated with a positive impact on cardiovascular health and reduction of high blood pressure [ 19 , 48 , 49 ]. However, ACE-I, renin, DPP-IV and PAF-AH are enzymes that are also present in the gut, and recent evidence suggests that inhibition of these enzymes can impact positively on gut health and may help to prevent necrosis, ulcerative colitis and other inflammatory disorders of the human gut [ 8 , 9 , 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the enzymes ACE-I, renin, PAF-AH and DPP-IV is known to lower systemic and local blood pressure, and assist in the alleviation of symptoms of several disorders including diabetes mellitus [ 7 ], hypercholesterolaemia, inflammatory diseases [ 8 , 9 ], and fibrosis [ 10 ]. Inhibition of ACE-I prevents the formation of angiotensin II, a potent vasoconstrictor while renin inhibition prevents the formation of angiotensin I, the precursor of angiotensin II [ 11 ].…”
Section: Introductionmentioning
confidence: 99%